Genetic diversity of Xanthomonas arboricola pv. pruni causing bacterial spot of stone fruit - Khoza, P. Khethiwe(Purity Khethiwe) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1999.